Security Analysis against Differential Cryptanalysis using Active S-Boxes - et. al., R.Kousalya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cryptography is a technique that uses mathematics for encryption of original data followed by decryption of encrypted data. Cryptography enables the impregnability of information while it passes through the Internet or wireless medium with more concern for security. It is highly challenging to execute the conventional cipher technique algorithms in a resource-constrained environment attributable to their size, speed and throughput. The Lightweight cipher technique is an algorithm that features a low footprint and computational complexity. In cipher methods, the substitution box acts major role in the encryption/decryption algorithm. The procedure of creating powerful S-boxes in cryptographic algorithm never end. Various methods are opened for creating a powerful S-box leading difficulty for an attack. This paper depicts a key-based dynamic Ssubstitution box for every round of encryption in PRESENT algorithm. Differential Cryptanalysis attack is verified with the quantity of active S-boxes in each round.